Analysis of Flexural Toppling Failure of Anti-Dip Rock Slopes Due to Earthquakes - Zhang, Hong; Wu, Yihan; Huang, Shiting; Zheng, Lu; Miao, Yuanbing (Frontiers in Earth Science, 2022)
Flexural toppling is one of the failure modes of anti-dip rocks, is often triggered by seismic load, occurs haphazardly under an earthquake scenario, and is characterized by high speed and extreme energy, leading to catastrophic disaster consequences and huge losses. However, there is limited literature that reveals its failure mechanisms and describes the failure surface due to earthquakes. Therefore, based on the limit equilibrium analysis method, the horizontal pseudo-static load was applied to improve the geological mechanical model under gravity only, and the stability analysis process was derived. The failure surface and failure mode of the slope under different seismic loads were analyzed. The results indicated that, with the increasing seismic load, an increase in the number of rock layers with sliding failure increased the number of rock layers with cantilever toppling failure; in contrast, the number of rock layers with overlapping toppling failure decreased. The slope toe was more prone to sliding and the slope top was more prone to cantilever toppling under an earthquake, which decreased the stability of the anti-dip rock slope.